Common Ownership and Equality of Autonomy - di Robilant, Anna (McGill Law Journal / Revue de droit de McGill, 2012)
In recent years, common ownership has enjoyed unprecedented favour among policy-makers and citizens in the United States, Canada, and Europe. Conservation land trusts, affordable-housing co-operatives, community gardens, and neighbourhood-managed parks are spreading throughout major cities. Normatively, these common-ownership regimes are seen as yielding a variety of benefits, such as a communitarian ethos in the efficient use of scarce resources, or greater freedom to interact and create in new ways. The design of common-ownership regimes, however, requires difficult trade-offs. Most importantly, successful achievement of the goals of common-ownership regimes requires the limitation of individual co-owners’ ability to freely use the common resource, as well as to exit the common-ownership arrangement.This article makes two contributions. First, at the normative level, it argues that common ownership has the potential to help foster greater “equality of autonomy”. By “equality of autonomy”, I mean more equitable access to the material and relational means that allow individuals to be autonomous. Second, at the level of design, this article argues that the difficult trade-offs of common-ownership regimes should be dealt with by grounding the commitment to equality of autonomy in the context of specific resources. In some cases, this resource-specific design helps to minimize or avoid difficult trade-offs. In hard cases, where trade-offs cannot be avoided, this article offers arguments for privileging greater equality of autonomy over full negative freedom.